ST Segment Elevation and Depressions in Supraventricular Tachycardia without Coronary Artery Disease - Fuad Habash; Arwa Albashaireh; Mohammed Eid Madmani; Hakan Paydak (Case Reports in Cardiology)
ST segment changes are well documented in literature during supraventricular tachycardias. We present a case of a 21-year-old male who presents with chest pain, shortness of breath, and dizziness with an ECG showing atrioventricular reentrant tachycardia and diffuse ST segment depressions. Patient spontaneously converted to sinus rhythm, but he was still complaining of crushing chest pain. ECG taken after conversion showed sinus rhythm at a rate of 65 and showed obvious persistence of ST depressions in majority of leads. Emergent left heart catheterization showed normal coronaries. Such ST depression is suggestive of global ischemia in small intracardiac vessels that cannot be evaluated by left heart catheterization.